Global citizenship and youth. Research inspired by the citizen science perspective - Adelina Calvo-Salvador; Renée DePalma-Úngaro; Carlos Rodríguez-Hoyos; Isabel Hevia-Artime (Revista Latinoamericana de Tecnología Educativa)
Citizen science enables the democratisation of knowledge and citizen collaboration in solving the global challenges we face as humanity. The participation of young people in this type of project strengthens their civic engagement and critical thinking, offering them the opportunity to become active agents of social change. In this article we present the theoretical framework and research methodology of a coordinated project of the National Research Plan that aims to promote the approach of education for global citizenship (GCE) through the involvement of young people in processes of enquiry that allow them to connect the local with the global. We aim to create scenarios where knowledge is generated from more horizontal, dialogical and shared logics, where young people can share their concerns, but also propose real actions and solutions. To this end, the YARGI (Young People as Researchers of Global Issues) methodological process has been designed based on a ten-stage method inspired by the movement of students as researchers. This research is particularly relevant in a field which has been criticised for a lack of research on how young people deal with global issues and what concerns them and moves them to action.